Diagnostic Value of Electronic Fetal Heart Rate Monitoring in Predicting the Neonatal Outcome (Medical Forum Monthly, 2020)
Objective: To Study the Diagnostic Value of Electronic Fetal Heartrate Monitoring in Predicting the Neonatal Outcome.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Gynae/Obs department Abbottabad international Medical College Abbottabad, Shaheena Jameel Teaching Hospital Abbottabad, Idris Teaching Hospital Sialkot and PAF Hospital Islamabad from July 2019 to Dec 2019.Materials and Methods: An admission cardiotography (CTG) was done for 20 minutes in all the cases and repeated at 4 hourly intervals. All the CTG traces were collected and interpreted according to Intenational Federation of Gynecology and Obstetrics (IFGO) guidelines as reactive, non-reactive and pathological. After delivery neonatal outcome was calculated using 5 min Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score and frequency of Neonatal Intensive care unit (NICU) admissions. The informed written consent was taking before history, examination and investigations. The permission of Ethical Committee was taken before collecting the data and get publishing in Medical Journal. All data was analyzed using SPSS Version 12.Results: All data was analyzed using SPSS Version 12. Out of 204 patients who qualified for the study, 68.1% had reactive traces, 26% had non-reactive traces and 5.9% had pathological traces. The APGAR score at 5 min and frequency of NICU admissions were lowest in reactive group, intermediate in non-reactive group and highest in pathological group. Regarding the mode of delivery, the highest percentage of caesarean deliveries was observed in pathological group (58.3%). The sensitivity (88.88%) of EFHRM was found to be higher than specificity (70.76%). The positive and negative predictive values were 12.30% and 99.28% respectively. Fisher’s exact test was applied between fetal heart patterns on CTG and 5 min APGAR score and the P value was found to be statistically significant.Conclusion: The results of this study demonstrate that cardiotography (CTG) is capable of discriminating healthy fetuses from those at risk of acidemia at birth and a statistically significant association exists between patterns of FHR and neonatal outcome. As a diagnostic test it has high sensitivity but low specificity and low positive predictive value, thus supplementation with additional tests may help gain maximum benefit and reduce unnecessary operative deliveries.